An epidemiological survey of Newcastle disease virus in South Africa - Mashope, Barbara Keitumetse (University of the Free State, 2001)
The primary objective in this study was the investigation of the molecular epidemiology of NDV strains isolated during epizooties in South Africa in 1998. Isolates purported to be NDV were collected from the Onderstepoort Veterinary Institute, the University of Pretoria, and EarlyBird Farms, Standerton. Four of the twenty-two isolates collected were identified as NDV, and successfully grouped into genotype VIIb, previously described by Herezeg et al., (1999). The isolates were propagated in 9-10 day-old embryonated SPF eggs. Embryo mortality was observed, allantoic fluid harvested, and genomic RNA extracted using TRIZOL ® reagent, containing guanidine thiocyanate. An RT-PCR based detection method was used to screen the isolates received (Ballagi- Pordány et al., 1996). The optimised method entailed initial reverse transcription in a reaction mixture containing IIlM random hexamers p(dN)6, 200 U Moloney Murine Leukemia (M-ML V) RT and 25 U RNasin. Aliquots of 5 ul, of the cDNA mix were used as template in subsequent PCR amplification reactions. A 1349bp region of the fusion protein gene was amplified using primers ONDVlaa and ONDV 4aa. Fusion protein amplicons were obtained from field isolates, M89/98 (Ost Pool I), M89/98 (Av Pool 2), M57/98, and M308/98 obtained from OP. Restriction enzyme profiles of the fusion protein amplicons using restriction enzymes HinfI, BstO I, and Rsa I displayed fragment patterns that allowed their grouping into genotype VIIb, described by Herezeg et al., (1999). Non-group specific bands observed upon digestion of the amplicon of strain M308/98 with Hinf I released fragments not consistent with those observed in genotype VIIb isolates. These fragments suggest the presence of mutations in this area of the genome. Amplification of a region comprising 88% of the matrix protein gene was facilitated using primers Ml and M2. These amplicons were subjected to RE analysis using restriction enzymes Mbt) I and Hinf I. Analysis of the restriction profiles produced revealed that these four strains were not re-isolated forms of the commonly used live vaccine LaSota strain. A region of the fusion protein gene encoding the fusion protein cleavage activation site was amplified by means of a nested peR, and sequenced. Initial peR amplified a region spanning from the M gene nt 778 to F gene nt 545 using primers Kl and K2. These amplicons were purified and used as template in a nested peR using primers MV1 (M gene nt 1163) and B2 (F gene nt 470). Sequence analysis revealed that the amino acid sequence at the fusion protein cleavage site of strains M89/98 (Ost Pool I), M57/98,and M308/98 was RRQKR -l-F, indicative of velogenie strains. Strain M89/98 (Av Pool 2) displayed a sequence at the fusion protein cleavage site that is characteristic of lentogenie strains GRQGR-l-L. This finding suggests that genotype VIIb isolates are heterogeneous, composed of strains of varying pathogenicity . Phylogenetic analysis based on a 378nt long region of the nested peR amplicon allowed the grouping of all these isolates into genotype VIIb. A 1.5-1% divergence was observed between group VIIb isolates collected in 1993, and 1995, and those used in this study, collected in 1998. This genetic distance is consistent with a 0.5-1% divergence in strains per year. The remaining field strains not detected by RT-peR, but that displayed embryo mortality indicative of pathogenic agents were subjected to HAlHI tests. Strains M193/98 (Ost Pool 6), M183/98 (Ost Liv B), and M193/98 (Ost Pool 5) agglutinated chicken erythrocytes. Haemagglutination was not inhibited by anti-NDV serum. These results led to the suspicion of the presence of an unidentified pathogen, most likely avian influenza, as all three samples were collected from ostrich hosts, from which this virus has previously been isolated in South Africa.

Die primêre doelwit van hierdie studie was om stamme van die epidemologiese Newcastle-siekte virus (NDV) wat tydens gelokaliseerde uitbreke van Newcastle-siekte in Suid-Afrika gedurende 1998 geïsoleer is, op molekulêre vlak te ondersoek. Sogenaamde NDV isolate is vanaf Onderstepoort Veeartsenykunde Instituut, Universiteit van Pretoria en Early Bird Plase, Standerton verkry. Slegs vier van die twee-en-twintig isolate kon as NDV geiïndentifiseer word en suksesvol as genotipe VIIb volgens beskrywing deur Herezeg et al. (1999) geklassifiseer word. Vermeerdering van die isolate is bewerkstellig deur kweking in 9-10 dag-oue bevrugte spesifiek patogeenvrye (SPV) eiers. Die tydperk voor die afsterwing van die embrio is aangeteken. Hierna is allantoïse vloesftof uit die eier onttrek en totale RNA met behulp van guanidien tiosianiedbevattende TRIZOL ® geïsoleer. Sifting van die isolate is bewerkstellig deur middel van die tru-transkriptase polimerase kettingreaksie (RT-PCR) metode (Ballagi-Pordány et al., 1996). In die geoptimiseerde RT-PCR metode is die boodskapper RNA (mRNA) in vitro omgeskakel na cDNA in 'n reaksiemengsel wat 1) LMewekunsige heksanukleotiede, p(dN)6, 200 eenhede Moloney Murien Lukemia Virus tru-transkriptase (M-MLV RT) en 25 eenhede ribonuklease stremmer (RNasin) bevat het. 5).LI hoeveelhede van die gevormde cDNA is as substraat vir die daaropvolgende polimerase kettingreaksies (PKR) gebruik. Inleiers ONDVlaa and ONDV4aa is gebruik om 1349 basispare (bp) van die fusieproteïengeen van die virus te amplifiseer. Fusieproteïen PKR-produkte is verkry vir veld-isolate M89/98 (Ost Pot I), M89/98 (Av Pot 2), M57/98 en M308/98, verkry vanaf Onderstepoort. Ontleding van Hinf I, BstO I, en Rsa I restriksie-ensiemsnydings van hierdie fusieproteïen PKR-produkte het daartoe aanleiding gegee dat die isolate waarvan dit verkry is as genotipe VIIb geklassifiseer kon word soos beskryf deur Herezeg et al. (1999). Die nie-groep VIIb spesifieke fragmente wat waargeneem is nadat die PKR produk van stam M308/98 met Hinf I verteer is, het tot die gevolgtrekking gelei dat moontlike mutasies in hierdie gebied van die genoom van M308/98 voorkom. Amplifikasie van 'n gebied wat 88% bestaan, is deur middel van PKR met behulp van inleiers Ml en M2 verkry. Ontleding van die fragmente verkry na MbO I en Hinf I restriksie-ensiemsnydings van die onderskeie PKR-produkte, het daarop gedui dat die betrokke stamme nie hergeïsoleerde vorms is van die LaSota stam wat in lewende entstof gebruik word nie. Deur middel van beskutte inleierbenadering is die gebied van die fusieproteïngeen wat vir die fusieproteïen-splytingsaktiveringsetel kodeer, geamplifiseer en die basisvolgorde daarvan bepaal. Die eerste stel inleiers, Kl en K2, het amplifisering vanaf nukleotied 778 van die M-geen tot nukleotied 545 van die F-geen ingelei. Hierdie PKR-produkte is gesuiwer en as substraat gebruik met die tweede stel inleiers MVl en B2 wat tot amplifisering vanaf nukleotied 1163 van die M-geen tot nukleotied 470 van die F-geen tot gevolg gehad het. Die aminosuurvolgorde soos afgelei uit die nukleotiedvolgorde van die fusieproteïensplytingsaktiveringsetels van stamme M89/98 (Ost Pot I), M57/98 en M308/98 was RRQKR. j,F wat aandui dat hierdie stamme velogenies is. Die aminosuurvolgende, GRQGR. j, L, van die fusieproteïen-splytingsaktiveringsetel van stam M89/98 (Av Pot 2) was kenmerkend van lentogeniese stamme. Hierdie bevinding dui daarop dat genotipe VUb isolate heterogeen is en dat die groep saamgestel is uit stamme met wissselende patogenisiteit. Filogenetiese ontleding, gegrond op die 378 bp fragment verkry met beskutte inleierbenadering, groepeer die genoemde isolate in genotipe VUb. Die groep VIIb isolate wat in 1993 en 1995 versamel is, toon 'n afwyking van 1-1.5% ten opsigte van die isolate wat in 1998 versamel en in hierdie studie gebruik is. Hierdie genetiese afstand is in ooreenstemming met 'n 0.5-1% afwyking in stamme per jaar. Die oorblywende veldisolate wat die dood van embrio's net soos die patogeniese agente kon veroorsaak, maar wat nie deur middel van tru-transkriptase PKR opgespoor kon word nie, is aan HAlHI toetse onderwerp. Stamme M193/98 (Ost Pot 6), M183/98 (Ost Liv B) en M193/98 (Ost Pot 5) het 'n agglutinasie van hoender rooi-bloedselle veroorsaak. Haemagglutinasie was nie deur die byvoeging van anti-NDV serum vertoed nie. Hierdie resultate het die vermoede laat ontstaan dat 'n ongeïdentifiseerde patogeen teenwoordig was, waarskynlik voëlgriepvirus, veralomdat al drie hierdie monsters vanaf volstruisgashere versamel is, waaruit hierdie virus al voorheen in Suid-Afrika geïsoleer is
Dissertation (M.Sc. (Microbiology and Biochemistry))--University of the Free State, 2001
Keywords: Molecular virology; Poultry -- Virus diseases -- South Africa; Newcastle disease -- Epidemiology -- South Africa